Effectiveness of stretching exercises in conservative therapy of plantar fasciitis (PF) - Kowal, Alicja; Spozowski, Karol (Journal of Education, Health and Sport, 2022)
Introduction and objective: Plantar fasciitis affects both young active patients and older people leading a sedentary lifestyle. It is result from chronic overload of the plantar fascia. About 80% of patients with plantar fasciitis improve within 12 months with non-surgical treatment. Nonsurgical management includes e.g. activity modification, cooling, non-steroidal anti-inflammatory drugs, stretching and strengthening exercises and manual therapy. Materials and methods: PubMed database was searched. The criteria for qualifying the articles for the review were the following keywords: plantar fasciitis, muscle stretching, exercise, manual therapy, heel spur. 11 articles from 2017 to 2022 were analyzed. Description of the state of knowledge: Calf stretching is one of the treatments for plantar fasciitis with the best results in the long run. In turn, strengthening exercises turn out to be more effective in a short time. One should also not forget about influence other methods of conservative treatment, such as cooling, orthoses or physical therapy, that support and accelerate the treatment process. Summary: Strengthening exercises of the plantar fascia are more effective than stretching in terms of reducing pain and improving function in the short term, while stretching exercises show better results in the long term. The best results are obtained by combining stretching of the triceps calf muscle with other methods of conservative treatment. There are no studies supporting the hypothesis that stretching alone is more effective in the treatment process than other methods and placebo.